Overconfidence among professional investors: Evidence from mutual fund managers - Alexander Pütz; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2010)
We examine overconfidence among equity mutual fund managers. While overconfidence has been extensively documented among retail investors, evidence from professional investors is scarce. Consistent with theories of overconfidence, we find that fund managers trade more after good past performance. The higher trading activity after good performance is driven by individual portfolio performance, while the market performance has no significant impact. We rule out some alternative explanations for our results like increased trading as a response to tournament incentives, as a response to inflows, or as a rational reaction due to managerial learning about abilities.
Keywords: D83; G10; G12; 330; professional investors; overconfidence; behavioral biases; mutual funds